EKTIVITAS PROGRAM JEMPUT BOLA (JEBOL) DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL (DISDUKCAPIL) DALAM MENGOPTIMALKAN PELAYANAN KEPENDUDUKAN DI KABUPATEN MUNA - Adawia, Andi Rabia; Ansari, Isa; Riskasari, Riskasari (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
This study aimed  to find out the effectiveness of the Population and Civil Registration Service (JEBOL) Program for Population and Civil Registration (DISDUKCAPIL) in optimizing population services in Muna Regency, which was a form of research that aimed to provide an overview as to the types of data collected from the field objectively with a qualitative descriptive type. Data collection techniques used observation, interviews with a number of informants. Data analysis using interactive analysis model. The results showed that the effectiveness of the E-KTP service in setting targets  was right on target, which was intended for people in Muna Regency with special needs, the elderly, and people who had met the requirements for recording E-KTP. The socialization of the program was carried out by the implementing team at the location that had been determined for the service of the Ball Pick-up  program. Monitoring of this program was carried out directly by the implementing team and indirect monitoring by means of data evaluation by the Head of the Population and Civil Registration Office of Muna Regency.